2012
DOI: 10.1097/ico.0b013e3182261577
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Optical Coherence Tomography–Derived Assessments of Lower Tear Meniscus Parameters and Clinical Features of Dry Eye Disease

Abstract: Purpose To measure the correlation between subjective symptom score, conventional clinical tests, and Fourier-domain optical coherence tomography (FD-OCT) of lower tear meniscus parameters in patients with dry eye disease. Methods Eighteen patients with dry eye disease requiring medical therapy and/or punctal occlusion were recruited for this prospective, nonrandomized, observational case series. Severity of symptoms of dry eye disease was assessed using the Indiana Dry Eye Questionnaire 2002. Clinical asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 48 publications
1
39
0
5
Order By: Relevance
“…On the other hand, correlation between Schirmer value and tear parameters were rather variable in a number of studies. Chen et al 36 found that Schirmer tests were not correlated with tear parameters, while Nguyen et al 39 found that tear parameters were significantly high correlated with Schirmer's test. Other studies described low 12,16 or moderate 13,15,38 correlation between Schirmer tests and tear parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, correlation between Schirmer value and tear parameters were rather variable in a number of studies. Chen et al 36 found that Schirmer tests were not correlated with tear parameters, while Nguyen et al 39 found that tear parameters were significantly high correlated with Schirmer's test. Other studies described low 12,16 or moderate 13,15,38 correlation between Schirmer tests and tear parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, in previous dry eye studies have been already showed various correlation rates between conventional tests and tear parameters. In these studies, the authors described low 12,13,15,36,38 or moderate 17,38,39 correlation (r = 0.218-0.450 and r = 0.510-0.602, respectively) between TBUT and tear parameters. On the other hand, correlation between Schirmer value and tear parameters were rather variable in a number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20 GM parametrelerinin Schirmer testi ile iyi korelasyon göstermesi beklenen bir sonuçtur çünkü Schirmer testi gözyaşı yapımını ölçmektedir ve GM parametreleri gözyaşı hacmi ile ilişkilidir. 6,21 Bu iyi korelasyon hastaya irritasyon yapması ve değişen oranlarda refleks yaşarmayı uyarması nedeniyle zaman zaman klinisyeni sıkıntıya sokan Schirmer testinin yerine OKT ile GM parametrelerinin invazif olmadan değerlendirilmesinin kullanılabilirliğini desteklemektedir.…”
Section: Discussionunclassified
“…Nguyen ve ark. 20 GKZ ile GM parametreleri arasında anlamlı bir ilişki olmadığını belirtirken Czajkowski ve ark. 17 özellikle GMY ile daha belirgin olmak üzere GKZ ile her 3 parametrenin de ilişkili olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…They have been shown to be significantly reduced in patients with Sj€ ogren syndrome (Qiu et al 2012), and their values have been shown to be positively correlated with the Schirmer test results (Nguyen et al 2012;Fukuda et al 2013). Thus, these two parameters are the dimensions used to calculate the tear volume.…”
Section: Discussionmentioning
confidence: 99%